Failure of International Agreements in Confronting Environmental Crimes: A Case Study of the Climate Crisis in Vanuatu - Misliharira Shaumi Putri; Ni Made Martini Puteri (CV. Publikasi Indonesia, 2024)
The fossil fuel non-proliferation agreement comes in response to the escalating climate crisis threatening Vanuatu, which was raised by the President of Vanuatu at the 77th General Assembly of the United Nations. This article analyzes the failure of international agreements as an effort to prevent environmental crimes that cause the global climate crisis, especially those felt by Vanuatu, as well as the extent to which international agreements can play a role in addressing these problems, as well as safeguarding the well-being of people in affected countries. The use of fossil fuels, which is still the primary energy in various countries, has become a focus in the context of environmental crimes because of its negative impact on the environment, including the climate crisis. Although these efforts are considered a step in the face of environmental crimes, their implementation is still limited. From a criminological perspective, the restriction of action through the law is a common approach to tackling crime. However, the issue of environmental crimes and international agreements shows the complexity involving many stakeholders. Taking into account the urgency of addressing the climate crisis and its impact on human rights, countries are expected to prioritize people's well-being. Through literature analysis, this article concludes that international treaties will not be effective in tackling environmental crimes without the support of domestic laws and policies, as well as the commitment of state leaders.